Technologie výroby součásti - Straka, Jiří (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2012)
Diplomová práce vytvořená v rámci magisterského studia M21-K Strojní inženýrství, oboru M-STM řeší technologii výroby strojní součásti Tvarové víko. Je proveden rozbor technologie výroby strojní součásti za použití konvenčních metod a alternativně některé z nekonvenčních metod obrábění. Tvarové víko je doposud vyráběno na klasických obráběcích strojích, což je pracné a ekonomicky nevýhodné. Je navržena nová technologie výroby, kde polotovar bude obroben nekonvenčním obráběním a dále pak bude obráběna na CNC konvenčním stroji. Nekonvenční technologií je navrženo obrábění elektroerozivní, paprskem plazmy a vodním paprskem. Konveční technologií je součást vyráběna na CNC obráběcí frézce. Dále je posouzeno technicko-ekonomické hodnocení navržené nové technologie.

This diploma thesis is developed within my Master’s degree studies, branch mechanical engineering (M21 K), and specialization in M STM. The aim of this thesis is to solve the technology of mechanical production (machining, tooling) for the machine component called ‚shape lid‘. I execute the analysis of this technology from the perspective of the conventional machining process, and alternatively, some of the non conventional machining process, too. Conventional machining process is so far used for manufacturing of this sort of machine’s element. It‘s implying laborious work difficulties, even it’s economically disadvantageous. I suggest a new technology of manufacturing. At first, a semi-finished component could be sized by conventional machining process, and then it could be finished by the CNC (computer numerical control) milling machine. By the non-conventional machining process assume the usage of an electro-erosive machining, plasma machining, or water jet machining.Conventional technology suppose the usage of CNC milling machines. Thereinafter, feasibility aspects of this brand new technology are considered in technical and economical perspective.
Technology of production part
Keywords: Konvenční technologie; nekonvenční technologie; obrábění; elektroerozivní obrábění; obrábění paprskem plazmy; obrábění vodním paprskem; CNC obráběcí frézka.; Conventional machining technology; non-conventional machining technology; machining; tooling; surfacing; plasma machining; water jet machining; CNC milling machine.